New Normal as The New Human: Masa Pandemi dalam Perspektif Filsafat Manusia Soren Aabye Kierkegaard dan Relevansinya pada Kehidupan Manusia Masa Datang - Fuad Noorzeha (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2020)
This paper is an exposition of Sören Aabye Kierkegard’s concept existentialist, a concept of the human existance into three distinctive levels, namely: the aesthetic existance, the ethics existance, the religious existance. These levels will affect the human existance and it is its way. These thought used be perspective about crisis or emergency situation during the pandemic Covid-19. The problems also have touched values of human rights, such as: social distancing, isolation, new normal and lockdown that eventually plunged the man into a social status problem. Those basic or fundamental problem are about fact a existance of man around social community. To give the answers, it is needed and approach which orientates to human existence. It can be found in thought of Sören Aabye Kierkegard he differs from other existentialist philosophers who in general are atheists. This paper seeks to reorient the meaning “new human” by library research with the existance approach of Sören Aabye Kierkegard at new normal era , the process of individualization in invividual interaction with the other human and the appreciation and religious practices when pandemic to limited with country rules. Revitalization of religion is needed to restore the basic values of religion. Religion must come back as a legitimate sovereign social values and piety. This sovereignty of religion should be structured as a strategy for revitalizing religion in the lives of individual piety personally and socially. However, the sovereignty of religion should give a wide freedom for individuals to perform the fuction of religion in accordance with the present context. Furthermore, the most crucial problem when pandemic must be solved by humane return to their a fact existance of human.